2013
DOI: 10.1097/mlr.0b013e31828d1210
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Frontier of Electronic Health Record Surveillance

Abstract: Background The aim of this study was to build electronic algorithms using a combination of structured data and natural language processing (NLP) of text notes for potential safety surveillance of nine post-operative complications. Methods Post-operative complications from six medical centers in the Southeastern United States were obtained from the Veterans Affairs Surgical Quality Improvement Program (VASQIP) registry. Development and test datasets were constructed using stratification by facility and date o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 34 publications
2
82
0
Order By: Relevance
“…The use of the EMR has considerable potential to improve institutional performance, including decreasing the readmission rate for prevalent conditions such as AMI. [11][12][13] Because EMRs are widely adopted, predictive models that exploit these resources could be seamlessly integrated into clinical pathways, offering an inexpensive tool to assist clinicians in assessing risk. However, the dataset in a comprehensive EMR is complex and unless methods are developed to interpret and present data, the full benefit of the EMR may not be realised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the EMR has considerable potential to improve institutional performance, including decreasing the readmission rate for prevalent conditions such as AMI. [11][12][13] Because EMRs are widely adopted, predictive models that exploit these resources could be seamlessly integrated into clinical pathways, offering an inexpensive tool to assist clinicians in assessing risk. However, the dataset in a comprehensive EMR is complex and unless methods are developed to interpret and present data, the full benefit of the EMR may not be realised.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In the present study we examined all the available administrative hospital factors associated with readmission in a cohort of patients admitted with AMI to a large regional hospital in Geelong (Vic., Australia). We used data from the EMR to derive and internally validate a model to predict unplanned ischaemic heart disease (IHD) readmissions over a 30-day period and all-cause readmission over 12 months after an admission with AMI.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 More recent NLP innovations have used keyword searching and other techniques to facilitate quality and safety monitoring in a variety of healthcare settings. 7,8 Despite these early applications, although, NLP remains a nascent technology in healthcare. Most of its current successes are restricted to research settings and have served more as a supportive technology to supplement the analysis of largely structured data rather than a standalone tool.…”
Section: Article See P 477mentioning
confidence: 99%
“…(12) In this scenario, studies have shown that active surveillance of changes in serum creatinine and urine output can automate alerts, guide the dosing of drugs, reduce the incidence of acute kidney injury, improve patient safety and help with identifying the occurrence of complications. (13,14) The objective of this study was to identify the occurrence of acute kidney injury in the postoperative period of cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%